Analisis Kesalahan Berbahasa dalam Karangan Narasi Siswa Kelas V SDN Cilengkrang Kabupaten Sumedang - Martini, Avini (Jurnal Artikula, 2019)
This research was intended to describe the errors in narrative essays on 5th grade students of SDN Cilengkrang, Sumedang Regency. Observation results showed some of the problems, such as students found it difficult to express ideas so that it was difficult to write essays, students didn’t respond well so that they looked unhappy and less active in learning. Based on those problems, the impact on student outcomes was greater which causes errors at the level of morphology, phonology, syntax, semantics, and spelling. Errors that could occur due to students' lack of understanding of good and correct spelling. This research was a preliminary study specifically designed to describe errors in narrative essays on elementary school students in Sumedang Regency. The long-term goals of the results of this study, could be used in the learning process by using models and learning methods that could minimize the problems done by students. In addition, the results of this study could create teaching materials that could bring out student’s motivation in writing essays. The method used in this research was descriptive. This method explained the recently phenomena through the collection of data obtained. The results of the analysis obtained data from six primary schools namely, SDN Cilengkrang.